Effects of curcumin supplementation on metabolic parameters, inflammatory factors and obesity values in women with rheumatoid arthritis: A randomized, double‐blind, placebo‐controlled clinical trial - Pourhabibi‐Zarandi, Fatemeh; Rafraf, Maryam; Zayeni, Habib; Asghari‐Jafarabadi, Mohammad; Ebrahimi, Ali‐Asghar (Phytotherapy research, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to cartilage damage with mostly accompanied by metabolic disorders. This study aimed to investigate the effects of curcumin supplementation on metabolic parameters (lipid profile and glycemic indices), inflammatory factors, visfatin levels, and obesity values in women with RA. This randomized, double‐blind, placebo‐controlled clinical trial was conducted on 48 women with RA. The patients were treated with curcumin (500 mg once a day) or placebo for 8 weeks. Fasting blood samples, anthropometric measurements, dietary intakes, and physical activity levels of subjects were collected at baseline and the end of the study. Curcumin supplementation significantly decreased homeostatic model assessment for insulin resistance (HOMA‐IR), erythrocyte sedimentation rate, serum levels of high‐sensitivity C‐reactive protein and triglycerides, weight, body mass index, and waist circumference of patients compared with the placebo at the end of the study (p < .05 for all). HOMA‐IR and triglyceride levels significantly increased within the placebo group. Changes in fasting blood sugar, insulin, other lipids profile, and visfatin levels were not significant in any of the groups (p > .05). These results support the consumption of curcumin, as a part of an integrated approach to modulate metabolic factors, inflammation, and adiposity in women with RA.